Anti-hepatitis B virus (HBV) response of imiquimod based toll like receptor 7 ligand in hbv-positive human hepatocelluar carcinoma cell line. Issue 1 (December 2017) - Das, Dipanwita; Sengupta, Isha; Sarkar, Neelakshi; Pal, Ananya; Saha, Debraj; Bandopadhyay, Manikankana; Das, Chandrima; Narayan, Jimmy; Singh, Shivaram; Chakrabarti, Sekhar; Chakravarty, Runu
Abstract Background Toll like receptors (TLRs) play an important role in innate immunity and various studies suggest that TLRs play a crucial role in pathogenesis of hepatitis B virus (HBV) infection. The present study aims in looking into the status of crucial host and viral gene expression on inciting TLR7. Methods The transcription of TLR7 pathway signaling molecules and HBV DNA viral load were quantified by Real Time-PCR after stimulation of TLR7 with its imiquimod based ligand, R837. Cell cycle analysis was performed using flow-cytometry. Expression of TLR7 and chief cell cycle regulator governing G1/S transition, p53 was also seen in liver biopsysss samples of CHB patients. HBV induced alteration in histone modifications in HepG2 cells and its restoration on TLR7 activation was determined using western blot. Results The TLR7 expression remains downregulated in HepG2.2.15 cells and in liver biopsy samples from CHB patients. Interestingly HBV DNA viral load showed an inverse relationship with the TLR7 expression in the biopsy samples. We also evaluated the anti-viral activity of R837, an agonist of TLR7. It was observed that there was a suppression of HBV replication and viral protein production upon TLR7 stimulation. R837 triggers the anti-viral action probably through the Jun N-terminal Kinase (JNK) pathway. We also observed a downregulation of histone H3K9Me3 repression mark upon R837 treatment in HBV replicating HepG2.2.15 cells, mimicking that of un-infected HepG2 cells. Additionally, the G1/S cell cycle arrest introduced by HBV in HepG2.2.15 cells was released upon ligand treatment. Conclusion The study thus holds a close insight into the changes in hepatocyte micro-environment on TLR7 stimulation in HBV infection.